Mutation spectrum of the SCN1A gene in a Hungarian population with epilepsy. (January 2020) - Till, Ágnes; Zima, Judith; Fekete, Anett; Bene, Judit; Czakó, Márta; Szabó, András; Melegh, Béla; Hadzsiev, Kinga
Highlights: Hungarian patients presenting Dravet syndrome were screened for SCN1A mutation. Fifteen novel point mutations of SCN1A gene were found with Sanger sequencing. Gross gene deletion were identified in three patients with Dravet syndrome. Clear relationship between phenotype and genotype could not be found. Abstract: Purpose: The vast majority of mutations responsible for epilepsy syndromes such as genetic epilepsy with febrile seizures plus (GEFS+) and Dravet syndrome (DS) occur in the gene encoding the type 1 alpha subunit of neuronal voltage-gated sodium channel ( SCN1A ). Methods: 63 individuals presenting with either DS or GEFS + syndrome phenotype were screened for SCN1A gene mutation using Sanger sequencing and multiplex ligation-dependent probe amplification (MLPA). Results: Our research study identified 15 novel pathogen mutations in the SCN1A gene of which 12 appeared to be missense mutations with addition of two frameshift-deletions and one in-frame deletion. The distribution of clinical phenotypes in patients carrying SCN1A mutations was as follows: twelve patients had classical DS, three patients had GEFS + syndrome and two relatives of DS patients were suffering from febrile seizures. Conclusions: Our study highlights the phenotypic and genotypic heterogeneities of DS and GEFS + with the important aim of gaining a deeper understanding of SCN1A -related disorders. This study also represents the first genetic analysis of the SCN1A gene in a Hungarian cohort with the DS and GEFS + syndrome phenotype.